2017
DOI: 10.1021/acs.jpcb.7b10480
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I) Chelators for Alzheimer’s Disease

Abstract: A component of the neurotoxicity of the beta amyloid peptide (Aβ) of Alzheimer's disease is its ability to generate superoxide, hydrogen peroxide, and hydroxyl radicals by reaction of its reduced copper complex Aβ/Cu with molecular oxygen. The objective of the present work was to devise compounds, L, that could remove Cu from Aβ/Cu, with the property that L/Cu itself would not be capable of reducing O or hydrogen peroxide. We show by density functional calculations that several pincer-type compounds with two i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…SGC1, though a potential β-sheet blocker, cannot stop copper binding to Rec. Ab initio electronic structure calculations on the dihistidine region of Rec, His 13 His 14 , indicated that Rec (and Aβ) would bind Cu­(II) and Cu­(I) with high affinity, Δ G bind = −55 kJ mol –1 and Δ G bind = −73 kJ mol –1 , respectively, with computed reduction potential, E o = 0.39 V vs NHE . These values are in acceptable agreement with experimental values for Aβ(1–40) and Aβ(1–16), Δ G bind = −50 to −60 kJ mol –1 and Δ G bind = −83 to −85 kJ mol –1 , for Cu­(II) and Cu­(I), respectively, with measured reduction potential, E o = 0.30 V vs NHE .…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…SGC1, though a potential β-sheet blocker, cannot stop copper binding to Rec. Ab initio electronic structure calculations on the dihistidine region of Rec, His 13 His 14 , indicated that Rec (and Aβ) would bind Cu­(II) and Cu­(I) with high affinity, Δ G bind = −55 kJ mol –1 and Δ G bind = −73 kJ mol –1 , respectively, with computed reduction potential, E o = 0.39 V vs NHE . These values are in acceptable agreement with experimental values for Aβ(1–40) and Aβ(1–16), Δ G bind = −50 to −60 kJ mol –1 and Δ G bind = −83 to −85 kJ mol –1 , for Cu­(II) and Cu­(I), respectively, with measured reduction potential, E o = 0.30 V vs NHE .…”
Section: Introductionsupporting
confidence: 68%
“…A previously designed 35 Cu + chelator, PI1, was elaborated by addition of a carboxylic acid amide group in the 4-position, yielding 4PI1. We showed by DFT calculations that 4PI1 when attached to a Glu residue, has high binding affinity for both Cu + and Cu 2+ , and a low-enough redox potential to prevent the generation of ROS (Figure 3c).…”
Section: ■ Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metal ions were recently considered a key factor closely related with Aβ aggregation [10]. Metal chelators regarded as potential lead compounds provide a whole new strategy for anti-AD approach [9,11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%